2017
DOI: 10.1115/1.4037641
|View full text |Cite
|
Sign up to set email alerts
|

An Experimental Study of Mist/Air Film Cooling With Fan-Shaped Holes on an Extended Flat Plate—Part 1: Heat Transfer

Abstract: Motivated by the need to further improve film cooling in terms of both cooling effectiveness and coolant coverage area, the mist/air film cooling scheme is investigated through experiments using fan-shaped holes over an extended downstream length in this study. Both an existing wind tunnel and test facility, used in previous work, have been retrofitted. The first modification was extending the length of the flat plate test section to cover longer distances downstream of the injection holes, up to X/D = 100, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…5 for the same Tu and BR. It has been observed that from X/D = 3 to X/D = 15, Mc = 7% yields the highest laterally averaged cooling effectiveness, representing an optimal parametric choice for near injection hole cooling, as highlighted in several previous studies [18,19]. However, within the region between X/D = 15 to X/D = 40, the laterally averaged effectiveness of Mc = 7% is surpassed by Mc = 4%.…”
Section: Effect Of Mist Concentrationmentioning
confidence: 60%
“…5 for the same Tu and BR. It has been observed that from X/D = 3 to X/D = 15, Mc = 7% yields the highest laterally averaged cooling effectiveness, representing an optimal parametric choice for near injection hole cooling, as highlighted in several previous studies [18,19]. However, within the region between X/D = 15 to X/D = 40, the laterally averaged effectiveness of Mc = 7% is surpassed by Mc = 4%.…”
Section: Effect Of Mist Concentrationmentioning
confidence: 60%
“…They mentioned that the bending back of air-mist coolant stream towards the blade surface is crucial in keeping the mist droplets close to the surface and, thus, enhance cooling effectiveness. Later, Ragab and Wang (2018) extended the study to understand the mist-air film cooling with fan-shaped holes over an extended flat plate. They observed an increase in laterally averaged cooling effectiveness and also in the extended downstream region when compared to cylindrical cooling hole.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that compared to the round hole, the oval hole reduces the strength of the main counter rotating vortex pair. Wang., 2018a, Ragab andWang., 2018b used infrared cameras and thermocouples to measure the temperature field and found that the newly incorporated fan-shaped film cooling hole had higher film cooling efficiency than cylindrical holes. Lee et al, 2021 experimentally investigated the effect of mainstream velocity on the optimization of a fan-shaped hole on a flat plate and found that the optimized hole showed a 49.3% improvement in the overall averaged film cooling effectiveness compared to the reference hole with DR 2.0 and M 2.0.…”
Section: Introductionmentioning
confidence: 99%